PENGARUH CITRA MEREK, PREFERENSI KONSUMEN, WORD OF MOUTH, KEPERCAYAAN, DAN PERSEPSI HARGA TERHADAP KEPUTUSAN PEMBELIAN JASA GO-RIDE (STUDI PADA MAHASISWA UNIVERSITAS DIPONEGORO) - Fitria, Fariza Dewi; Mahfudz, Mahfudz (Faculty of Economics and Business Diponegoro University, 2018)
Results from the initial findings of the interview found that Diponegoro university students were not satisfied with the services provided by Go-Jek, among others, apps are often error, the location of the remote driver, drivers pay less attention to passenger safety, and it is found that there is a gap between the number of downloaders and the number of Go-Jek transactions. This research was conducted to analyze the effect of brand image, consumer preference, word of mouth, trust and price perception on purchase decision Go- Ride service on Diponegoro University student.Data collection technique conducted in this study is a questionnaire. The sample was chosen by purposive sampling technique. Respondents in this research are Diponegoro University students who have used Go-Ride service for at least 2 times, with 110 respondents whose distribution includes 11 faculties. The technique used to analyze the influence of independent variables and dependent variable of this research is multiple linear regression analysis.Result of research prove that hypothesis one Brand image have positive effect to Purchase Decision accepted. The second hypothesis of Consumer Preference has a positive effect on Purchase Decision accepted. The third hypothesis of Word Of Mouth has a positive effects on Purchase Decision accepted. Fourth Hypothesis, Trust has a positive effect on Purchase Decision accepted. The fifth hypothesis, Price Perception has a positive effect on Purchase Decision accepted. Coefficient of determination test results stated that the five independent variables have an influence of 47.9% of Purchase Decision. Go-Ride service providers are advised to build a better brand image, by knowing their consumer preferences so that it is expected to create positive word of mouth and consumer confidence to improve purchasing decisions.